RE-READING HATTA'S THINKING IN MOVEMENT: BETWEEN ISLAM AND NATIONALISM - Rian Wahyudin (UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. This article reviews the perspectives of Mohammad Hatta as one of the Indonesian founding fathers in regards between Islam and nationalism. Many scholars, historians, and intellectuals have deemed that Hatta was a secular nationalist who separated national propositions from religious values. Whereas, on the contrary, both his actions and thoughts were in line with the noble of Islamic values, not only when he wanted to establish the Indonesian Islamic Democratic Party in 1967 with several other activists such as alumni of Islamic Students Association (HMI), PII, the Indonesian Islamic Syarikat Party, and Nahdlatul Ulama (NU) figures, but also Hatta's Islamic integrity already seen during the movement, when he was active in both the Indonesian Association (PI) organization in 1921-1930 and the Indonesian National Education (PNI Baru) in 1931-1932. For instance, Hatta proposed his thoughts on peace, which he took from Qur’an surah al-Fatihah verse two. According to him, the concept of peace is the highest law in Islam; therefore, every free nation must uphold peace. He continued, the statement